Exploring the Relationship Between TOEIC Listening and Reading Scores and Test-Taking Strategies Among University Students - Nakhon Kitjaroonchai; Tantip Kitjaroonchai (JET (Journal of English Teaching), 2026)
English proficiency remains a critical determinant of academic and professional readiness, with TOEIC serving as a key indicator of real-world communication skills. Understanding how listening and reading interact—and how test-taking behaviors shape outcomes—offers meaningful guidance for both instruction and assessment. This study investigated the relationship between TOEIC Listening Comprehension (LC) and Reading Comprehension (RC) scores and explores the test-taking strategies employed by high-scoring university students. Quantitative data were drawn from 727 TOEIC mock test records collected over four academic years at Asia-Pacific International University, while qualitative insights were obtained from reflective responses of 30 students scoring between 700 and 990. Pearson correlation analysis revealed a strong positive association between LC and RC (r = .899, p < .01), with LC accounting for 81% of the variance in RC scores (R² = .809), confirming listening proficiency as a significant predictor of reading performance. Correlations remained moderate across proficiency bands, though the LC–RC gap widened among lower scorers, indicating disproportionate weaknesses in reading. Thematic analysis identified seven strategy categories: strategic time management, pre-reading and predictive listening, selective attention, elimination and inference, focus and concentration control, emotional regulation and stress management, and test familiarity practices. Findings underscore the need for integrated receptive-skill instruction and holistic strategy training that combines cognitive, metacognitive, and affective approaches. These insights inform curriculum design and pedagogical interventions aimed at improving TOEIC outcomes and enhancing learners’ readiness for global communication.